Analisis Bibliometrik Tren Global Kajian Efisiensi Produksi Susu Sapi Perah - Malika, Uyun Erma; Sumarlina, Sumarlina; Wijaya, Jemi Cahya Adi; CNAWP, Rizal Perlambang; Putra, Mohammad Edwinsyah Yanuan (Universitas Galuh, 2025)
Milk is one of the important food sources for the community. Therefore, studies on the development of dairy cow milk production businesses have been carried out quite a lot, both nationally and globally. This study aims to determine the global trend of dairy cow milk production efficiency studies conducted using the bibliometric analysis method. The data used are scientific publications indexed on Google Scholar during the period 2014 - 2024 using the help of Publish or Perish, Mendeley Reference Manager, and VOSviewer software. The results of the study showed that publications related to dairy cow milk production efficiency studies has a positive trend with a tendency for study areas that can be grouped into socio-economic, production, environmental, and technology. In addition, there is a shift in the grouping of keywords used, namely that recent research focuses more on the quantity and quality of milk influenced by the treatment and formulation of feed in dairy cattle. The most widely used efficiency analysis research methods are Stochastic Frontier Analysis, Data Envelopment Analysis, and Cobb-Douglass Production Function. The results of this study provide an overview of further research opportunities related to dairy cow milk production efficiency with methods according to the needs.